Republican theology: the civil religion of American evangelicals - Lynerd, Benjamin T. (Oxford University Press, 2014)
Since the founding, American evangelicals have espoused a political theology that sees limited government as a condition for a thriving church and accordingly tilts toward libertarian politics. This 'republican theology', however, also predicates the republic's longevity on the church's capacity to elevate civic virtue, an impulse toward moral activism that often cuts against the libertarian grain. How evangelicals navigate the logic of their civil religion forms the subtext of their participation in American politics.